MODEL PENYELESAIAN SENGKETA WARIS DALAM MASYARAKAT ACEH - Sayuthi Sayuthi; Dedy Sumardi (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2021)
This article analyzes the models of the application of the theory of the inheritance dispute resolution in Bireuen community, Aceh. The inheritance dispute resolution in Aceh is not always done through the litigation system, but can also be done through non-litigation channels. This study is limited to the practice of the application of the alternative dispute resolution theories that took place in Bireuen community, Aceh, and describes the tendency of the Bireuen community to choose to resolve the inheritance disputes through the gampoeng justice system. The field data collection was carried out by observing the practice of dispute resolution in the community, and in-depth interviews with village officials and the disputing parties. The results show that the Bireuen community, Aceh tends to use the theory of negotiation, conciliation and facilitation through the customary justice system, namely the gampoeng court and the mukim court. Both of the gampoeng justice systems prioritize peaceful efforts and ensure privacy between family members. This principle is a consideration for the Bireuen community, Aceh chooses to resolve the inheritance disputes following the customary justice system compared to the official state justice system as a characteristic of the modern justice system implemented by the nation state.